2018
DOI: 10.1016/j.molp.2018.05.009
|View full text |Cite
|
Sign up to set email alerts
|

A Phytophthora capsici RXLR Effector Targets and Inhibits a Plant PPIase to Suppress Endoplasmic Reticulum-Mediated Immunity

Abstract: Phytophthora pathogens secrete a large arsenal of effectors that manipulate host processes to create an environment conducive to pathogen colonization. However, the underlying mechanisms by which Phytophthora effectors manipulate host plant cells still remain largely unclear. In this study, we report that PcAvr3a12, a Phytophthora capsici RXLR effector and a member of the Avr3a effector family, suppresses plant immunity by targeting and inhibiting host plant peptidyl-prolyl cis-trans isomerase (PPIase). Overex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
84
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 84 publications
(85 citation statements)
references
References 73 publications
0
84
0
1
Order By: Relevance
“…RXLR effectors have become a focus for studying plant–pathogen interaction in the past decade, with numerous effector genes identified and characterized in Phytophthora and downy mildew species (Tyler et al , ; Haas et al , ; Baxter et al , ; Yin et al , ). Many studies have reported that RXLR effectors are involved in the suppression of PTI and/or ETI (Wang et al , ; Kong et al , ; Fan et al , ) Additionally, some of them can trigger immune response‐related cell death, for example Phytophthora sojae Avh238 (Yang et al , ), Phytophthora capsici Avh1 (Chen et al , ), and Plasmopara viticola RXLR16 (Xiang et al , ).…”
Section: Introductionmentioning
confidence: 99%
“…RXLR effectors have become a focus for studying plant–pathogen interaction in the past decade, with numerous effector genes identified and characterized in Phytophthora and downy mildew species (Tyler et al , ; Haas et al , ; Baxter et al , ; Yin et al , ). Many studies have reported that RXLR effectors are involved in the suppression of PTI and/or ETI (Wang et al , ; Kong et al , ; Fan et al , ) Additionally, some of them can trigger immune response‐related cell death, for example Phytophthora sojae Avh238 (Yang et al , ), Phytophthora capsici Avh1 (Chen et al , ), and Plasmopara viticola RXLR16 (Xiang et al , ).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, multiple candidate proteins or their closely related orthologs have been shown implicated in diverse plant-microbe interactions. Rice chitinase 11 is a PR protein strongly induced by pathogen infection, and overexpression of the protein in transgenic rice plants enhances the resistance against sheath blight disease (Grover 2012;Kumar et al 2018); whereas the PPIases, which mediate protein folding in the endoplasmic reticulum, are targeted by pathogens to subdue plant defenses (Kromina et al 2008;Fan et al 2018). In contrast, OsWRKY28 has been identified as a negative regulator of immunity and can enhance susceptibility to blast disease when overexpressed in transgenic plants (Chujo et al 2013;Chen et al 2017); likewise, overexpression of the Arabidopsis heat shock cognate 70 (HSC70), sharing over 90% of sequence identity with the candidate rice heat shock cognate protein 2 found in this study, disables resistance to virulent pathogen strains including Hyaloperonospora parasitica Noco2 and Pseudomonas syringae pv tomato DC3000 (Noël et al 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Agrobacterium-mediated transient expression assay by infiltration was performed as described previously (Fan et al, 2018). Briefly, constructs were transformed into A. tumefaciens strain GV3101 (Rossi et al, 1993) by electroporation.…”
Section: Agroinfiltration and Inoculation Assaysmentioning
confidence: 99%